Blue laser diode-pumped Ce:YAG phosphor-coated cylindrical rod-based extended white light source with uniform illumination. (20th March 2019) - Dubey, Atul Kumar; Gupta, Mayank; Kumar, Virendra; Singh, Veena; Mehta, Dalip Singh
Abstract: We report the development of an extended white light source with uniform illumination using a cylindrical rod coated with Ce-doped YAG phosphor and excited by a blue diode laser. A long cylindrical rod made of transparent acrylic was first ground in order to diffuse laser light uniformly throughout the rod. Ce:YAG phosphor was then coated on the cylindrical rod and a blue color laser beam of 1 W power pumped into it. The laser beam propagates through the entire length of the rod via total internal reflection. This is possible because the laser light is highly directional and coherent with high brightness. To achieve a uniform scattering distribution of blue laser light throughout the length of the cylindrical rod, variations in grinding as well as making a hollow core inside the tube are reported. While propagating through the rod, the blue photons are also scattered out due to the rough scattering surface of the acrylic rod. Some of the blue photons are absorbed by yellow phosphor thus generating yellow color photons and the remaining blue photons are mixed with the yellow light generating white light. Such an extended light source acts as a conventional tubelight of 30 cm length. Due to this extended light source, the illumination is uniform and produces no glare as compared to high brightness laser-based point sources as well as LED-based white light sources. Since the phosphor is coated on the outside of the acrylic rod and laser power is distributed uniformly, the burning of phosphor is completely avoided. The light source was characterized by measuring Commission International de l'Eclairage coordinates and correlated color temperature. This kind of light source is highly useful for general purpose illumination.